Knowledge and skill level among non-healthcare providers regarding cardiopulmonary resuscitation (CPR) training in the Middle East (Arab countries): a systematic review and meta-analysis - Alsabri, Mohammed Alsabri Hussein; Alqeeq, Basel F.; Elshanbary, Alaa Ahmed; Soliman, Youssef; Zaazouee, Mohamed Sayed; Yu, Rebecca (BMC public health, 2024)
Background Effective education is considered by the American Heart Association (AHA) as a vital variable in improving outcomes of cardiac arrest. Studies have shown that the level of knowledge and attitude of non-healthcare providers towards resuscitation training varies widely across the globe. While some training methods and barriers to training have been discussed, the literature is still quite vague and unclear regarding resuscitation training, particularly in the Middle East. This study’s focus on the efficacy of resuscitation training in this region of the world may help dictate how to better implement education initiatives aimed towards non-healthcare providers in developing countries. Methodology A systematic review and meta-analysis were conducted on studies published from inception until March 2023. Observational studies assessing CPR knowledge and skills among non-healthcare workers in Arab countries were included. Data were extracted from PubMed, Cochrane Library, EMBASE, Web of Science, and Scopus. Data analysis was performed using Rstudio with a random effects model. Results 50 studies were included in this review and meta-analysis, revealing that 55% of participants had prior knowledge of CPR, while only 28% considered their knowledge sufficient. The majority (76%) supported mandatory CPR training, and 86% were willing to attend training if offered. This study found that prior knowledge of cardiopulmonary resuscitation (CPR) varied among populations. This meta-analysis also compiled results regarding CPR technique defined by correct compression to ventilation ratio, compression depth, compression rate, location of chest compression, and correct sequence. The overall results from this meta-analysis showed that, of these factors, compression rate and depth were the two factors that were most often administered incorrectly. In all, the results from this study demonstrated that CPR training in Arab countries was favorably viewed overall, with the majority of participants indicating both support for mandatory CPR training and general willingness to attend training if offered the opportunity. Conclusion Given the overall positive view and willingness to learn CPR skills, healthcare policy makers should adopt a more comprehensive focus on strategies that enhance the accessibility and opportunity for CPR training for non-healthcare populations in Arab countries. Future training programs should implement strategies to highlight the ideal combination of compression rates and depth to learners to ensure correct and efficacious delivery of CPR with increased focus on the practical portion during refresher courses to promote retention.